Recent developments in the nanomaterial-catalyzed green synthesis of structurally diverse 1, 4-dihydropyridines. Issue 3 (5th January 2021) - Mathur, Ritu; Negi, Khushal Singh; Shrivastava, Rahul; Nair, Rashmy
Abstract : Single pot multicomponent approaches using different nanomaterials as green catalysts for synthesis of 1, 4-dihydropyridine (1, 4-DHP), a privileged heterocyclic scaffold with vital biological and therapeutic applications are reviewed. Abstract : 1, 4-Dihydropyridine (1, 4-DHP), a privileged heterocyclic scaffold, has been extensively utilized in various biological and therapeutic applications. In this review article, we discussed the role of different nano-catalysts, nanoflakes, nanocomposites, and other green-supported nanomaterials in the synthesis of a biologically active and vital pharmaceutical precursor 1, 4-DHP and its derivatives such as polyhydroquinoline, benzopyranopyridines, and dihydropyridine since 2015. It is evident that although the use of various tailored nanostructures under different conditions to optimize the synthesis of 1, 4-DHP and its compounds has provided sustainable and efficient proposals, yet the development of greener practices in the synthesis of 1, 4-DHPs, which can be applied to design new synthetic routes and sequences in process development, is a far-reaching task to be accomplished.